Productive and reproductive performance of Siri cattle under field condition in West Bengal - ROY, RAKESH; TIWARI, RUPASI; DUTT, TRIVENI (The Indian Journal of Animal Sciences, 2021)
A study was undertaken with an objective to assess productive and reproductive performance of Siri cattle in West Bengal. The study was conducted among 80 farmers rearing either Siri-Pure or Siri-Graded cattle in the hilly region. Equal numbers of respondents either rearing Siri-Pure or Siri-Graded cattle were randomly selected from Darjeeling and Kalimpong districts for the study. The study on productive performance of Siri-Pure and Siri- Graded cattle shows that mean first lactation milk yield was 469.7 and 497.2 litres, daily milk yield was 3.2 and 3.7 litres, peak milk yield was 3.8 and 4.2 litres, total lactation milk yield was 864.1 and 1035.5 litres, lactation length was 273.4 and 284.8 days and dry period was 189.3 and 167.9 days. The t-test shows highly significant difference between Siri-Pure and Siri-Graded cattle in first lactation milk yield, daily milk yield, total lactation milk yield and lactation length in productive performance whereas age at first services, calving intervals and gestation period in reproductive performance. The reproductive performance of Siri-Pure and Siri-Graded cattle shows that mean age at first services was 38.47 and 31.65 months, gestation period was 285.2 and 279.1 days, heat interval was 27.8 and 28.2 days, number of services per conception was 1.3 and 1.3 times, and calving intervals recorded as 463.7 and 452.7 days respectively. The age at first service was significantly lower in large farmers and significantly higher calving interval in small farmers rearing Siri-Pure cattle. Daily milk yield, peak milk yield and total milk yield was significantly higher in large and medium farmers than small farmer rearing Siri-Pure cattle whereas total milk yield was significantly higher in large farmers than small and medium farmers rearing Siri-Graded cattle.